WH 1124: A new wheat variety for late sown irrigated conditions in north west plain zone of India - Singh, Vikram; Singh, Bhagat; Panwar, Ishwar Singh; Verma, Sada; Dalal, Mohinder; Saharan, Rajinder; Solanki, Yashpal; Bishnoi, Om; Karwsara, Surender (Journal of Cereal Research, 2025)
WH 1124, a new high yielding wheat variety has been developed and notified for late sowing under irrigated condition of north west plain zone (NWPZ) of India during 2014.The variety has average yield of 42.7q ha-1 and yield potential upto 54.1q ha-1.Â  It has semi erect growth habit medium height (avg. 91cm), hairy auricle and medium long, waxy, ear with a maturity period of 121 days. It possess resistance to rusts and tolerant to karnal bunt disease. It has good quality content and nutrient uptake. It is physiologically efficient genotypeÂ  with low heat susceptible ( 0.79) and high SPAD chlorophyll content (42.4) indicating its suitability under terminal heat stress conditions.